ANALISA FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN LANJUT USIA DI POSYANDU WILAYAH KERJA PUSKESMAS DODA KABUPATEN POSO - Meilani, Meilani; Adam, Arlin; Sainuddin, Sudirman; Zamli, Zamli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The coverage of health services in the elderly Poso Regency was 59,79% and the average elderly visits to Posyandu in the working area of Puskesmas Doda were only 47,3%. This research discusses factors related to elderly visits at Posyandu in the working area of Puskesmas Doda, Poso Regency. This study uses a cross sectional approach. The population in this study was 686 elderly people aged 60 years and over and registered in the elderly Posyandu in the working area of the Puskesmas Doda, Poso Regency. The sample in this study was 85 people selected using the simple random sampling method. Data analysis uses the Chi Square Test. The results of the study show a relationship between family support and elderly visits to Posyandu (p-value = 0,031), but there is no relationship between elderly perceptions (p-value = 0,729), the role of Posyandu officers (p-value = 0,151), and elderly visits to Posyandu. It is hoped that Puskesmas Doda will make innovations related to family support and further evaluation regarding other factors related to elderly visits.Keywords: eldery posyandu, visits, family support, perception, the role of posyandu officer